Comparison of High Order Abberations Between Laser in Situ Keratomileusis (LASIK) and Refractive Lenticule Extraction (ReLEx) Surgeries - Tri Wahyu; Susi Heryati (Majalah Oftalmologi Indonesia, 2020)
Background: The needs of refractive surgery with laser to correct refractive error (myopia, hyperopia, and astigmatism) have become more demanded. Eventhough the procedures can produce expected efficacy and safety, modification in corneal surface can affect optical and visual quality, resulting in visual distortion and artefacts (glare, halo, starburst) called high order aberrations (HOA). Objective: To report the differences of high order aberration before and after corneal ablation and refractive lenticule extraction surgery. Methods: This is an analytical retrospective observational study which conclude 60 patients (115 eyes) who underwent laser in situ keratomileusis (LASIK), femtosecond laser-assissted laser in situ keratomileusis (FS-LASIK), femtosecond lenticule extraction (FLEx), and small-incision lenticule extraction (SMILE) during the periode of January 2017 to August 2018. Results: Of 115 eyes, the mean of pre-operative high-order abberations were divided into four groups: LASIK was 7.27±3.85, FS-LASIK was 7.06±5.77, FLEx was 6.43±3.14, and SMILE was 3.73±1.41. Trefoil was the most common high-order abberations in pre-operative data of LASIK, FLEx, and SMILE (50.0%, 56.25%, and 51.72% respectively), while coma was mostly found in FS-LASIK (46.67%). Coma was the most common finding in first and third month after surgery. High-order aberrations between first and third month after surgery were not statistically significant different (p=0.465, p=0.889, p=0.263, and p=0.508 respectively). Conclusion: All types of procedures of corneal ablation and refractive lenticule extractions surgeries are effective and safe in correcting refractive errors. There were no differences of post-operative high- order aberrations in all types of procedures.